2018
DOI: 10.3389/fpsyt.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Nurse’s Exposure to Workplace Violence Leads to Job Stress, Which Leads to Reduced Professional Quality of Life

Abstract: Professional quality of life (ProQOL) reflects how individuals feel about their work as helpers. Psychiatric ward nurses cope with significant psychological and physical challenges, including exposure to verbal and physical violence. This study was based on two aspects of ProQOL, the positive compassion satisfaction, and the negative compassion fatigue, with the aim of investigating the relation of ProQOL to job stress and violence exposure at a large mental health center. Data were collected from 114 mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 40 publications
7
132
0
5
Order By: Relevance
“…Finally, experiencing workplace violence was another key variable associated with our primary outcomes. Workplace violence is associated with poor quality of life, increased staff turnover, BO and STS, and poor patient care outcomes in other studies (Arnetz et al ; Beck ; Itzhaki et al ; Lanctôt & Guay ). We found that both witnessing and experiencing workplace violence were significantly associated with poor CS and increased BO and STS scores.…”
Section: Discussionmentioning
confidence: 78%
“…Finally, experiencing workplace violence was another key variable associated with our primary outcomes. Workplace violence is associated with poor quality of life, increased staff turnover, BO and STS, and poor patient care outcomes in other studies (Arnetz et al ; Beck ; Itzhaki et al ; Lanctôt & Guay ). We found that both witnessing and experiencing workplace violence were significantly associated with poor CS and increased BO and STS scores.…”
Section: Discussionmentioning
confidence: 78%
“…[5][6][7][8] Importantly, it has been reported that the incidence of patient violence/related problems in psychiatric wards is 2-to 4 -times higher than that in general wards, 9 and nearly 90% of psychiatric nurses experience such violence. [10][11][12][13][14] Based on these findings, clinical psychiatric nurses are likely to deal with violence and offensive statements daily.…”
mentioning
confidence: 99%
“…In our sample the subjects exposed to violence reported a higher lack of energy and motivation score (subscale vi of the NWFQ) than their unexposed colleagues. Previous investigators have affirmed that WV can generate compassion fatigue and burnout (Itzhaki et al, 2018). Therefore, even if the cross‐sectional design of our study does not allow us to confirm any causal relationships, we can believe that, if the conditions of distress, violence, and perceived injustice should last for a long time, workers could be at risk for developing burnout.…”
Section: Discussionmentioning
confidence: 95%